2013
DOI: 10.1037/a0032288
|View full text |Cite
|
Sign up to set email alerts
|

Internationalizing the U.S. Undergraduate Psychology Curriculum: A Qualitative Investigation of Faculty Perspectives

Abstract: Owing to U.S. centrism, policy regulations, language barriers, institutional resistance, and faculty member interests, efforts to internationalize the undergraduate psychology curriculum are not yet realized. Therefore, we conducted a consensual qualitative research ( Hill, 2012 ; Hill et al., 2005 ; Hill, Thompson, & Williams, 1997 ) investigation of current efforts to internationalize the U.S. undergraduate psychology curriculum. We interviewed 15 faculty members (eight women, seven men) regarding their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Finally, it is important that internationalizing the undergraduate psychology curriculum considering the demands of the specific cultural contexts and multiculturalism have become a priority in structuring the undergraduate curricula (see Bikos, DePaul Chism, Forman, & King, 2013). Therefore, international awareness and cultural diversity have been accepted as the critical learning outcomes in undergraduate psychology education in the Western cultures (APA, 2013; Brewer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important that internationalizing the undergraduate psychology curriculum considering the demands of the specific cultural contexts and multiculturalism have become a priority in structuring the undergraduate curricula (see Bikos, DePaul Chism, Forman, & King, 2013). Therefore, international awareness and cultural diversity have been accepted as the critical learning outcomes in undergraduate psychology education in the Western cultures (APA, 2013; Brewer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most research related to internationalizing the curriculum has been criticized for being disjointed and lacking coherence (Barnett and Coate 2005 ; Leask 2013 ), with few studies situated in the USA. US-based studies tend to emphasize specific disciplines such as psychology (Bikos et al 2013 ), business (Manuel et al 2001 ), and counseling psychology (Marsella and Pedersen 2004 ).…”
Section: Understanding Internationalization Research Through An Equitmentioning
confidence: 99%
“…Consistent with our use of internationalizing, a qualitative study of faculty members identified core features of internationalizing psychology as (a) challenging Western privilege in psychology and notions that traditional psychology is a universal psychology as well as (b) emphasizing ways in which psychology is shaped and embedded within cultural contexts. In addition, (c) although internationalizing psychology includes cross-cultural study and comparisons, it also includes the study and valuing of indigenous psychologies (Bikos, Chism, Forman, & King, 2013). Given the multiple meanings assigned to the terms described in this section, it is important to be mindful that terms related to the study of culture are often interpreted through varied lenses and experiences.…”
Section: Terminology and Varied Approaches To The Study Of Culturementioning
confidence: 99%